2022
DOI: 10.3390/agriculture12030406
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings of Polypropylene Carbonate (PPC) Plastic Film Mulching Effects on the Soil Microbial Community

Abstract: The farmland residual film pollution caused by traditional PE film has an adverse impact on crops and the environment. Polypropylene carbonate (PPC) film is a fully biodegradable film that can alleviate “white pollution”. In this study, the soil physicochemical properties and the composition and function of the soil community of FM (PPC film mulching) and CK (no film) treatments were determined to explore the effect of PPC film mulching on soil and the soil microbial community. Furthermore, the microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…PPC is degraded by micro-organisms in the soil environment. Although degraded PPC increases the pH of soil, it does not significantly affect the richness of the microbial community in the soil [ 126 ]. Nevertheless, PPC degrades slowly under normal conditions and does not meet usage requirements.…”
Section: Applications Of Ppcmentioning
confidence: 99%
“…PPC is degraded by micro-organisms in the soil environment. Although degraded PPC increases the pH of soil, it does not significantly affect the richness of the microbial community in the soil [ 126 ]. Nevertheless, PPC degrades slowly under normal conditions and does not meet usage requirements.…”
Section: Applications Of Ppcmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectra were recorded on a Bruker DPX-400 spectrometer using deuterated chloroform (CDCl 3 ) as the solvent and tetramethylsilane as an internal standard. Differential scanning calorimetry S C H E M E 1 Ternary copolymerization of CO 2 , PO, and CH (DSC) was measured on a Mettler-Toledo 822 e thermal analyzer in a dry nitrogen environment.…”
Section: Characterizationsmentioning
confidence: 99%
“…Copolymerization of CO 2 with epoxides to generate aliphatic polycarbonate is a promising route. Poly(propylene carbonate) (PPC), synthesized by alternating copolymerization of CO 2 and propylene oxide (PO), shows exceptional properties, such as biodegradability, biocompatibility, and gas barrier, 11,12 attracting particular interest in the field of biomedicine, food packaging, and agriculture 12–15 . However, PPC is deficient in low glass transition temperature ( T g ), poor thermal stability, and low mechanical properties (e.g., low Young's modulus and tensile strength), which restrict its wide applications 14–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Film mulching can significantly increase soil microbial diversity and bacterial abundance [16]; it can also significantly increase the α-diversity of soil bacteria and have a crucial effect on shaping the soil bacterial community [17]. Bacterial networks in filmmulched soils are more complex and have a higher index of microbial community diversity than those in non-mulched soils [18]. It has also been shown that film mulching agricultural soils accelerates the succession of microbial communities in the soil and affects the stability and diversity of the soil microbial community structure [19].…”
Section: Introductionmentioning
confidence: 99%